2009
DOI: 10.1172/jci38443
|View full text |Cite
|
Sign up to set email alerts
|

HIF2α cooperates with RAS to promote lung tumorigenesis in mice

Abstract: Members of the hypoxia-inducible factor (HIF) family of transcription factors regulate the cellular response to hypoxia. In non-small cell lung cancer (NSCLC), high HIF2α levels correlate with decreased overall survival, and inhibition of either the protein encoded by the canonical HIF target gene VEGF or VEGFR2 improves clinical outcomes. However, whether HIF2α is causal in imparting this poor prognosis is unknown. Here, we generated mice that conditionally express both a nondegradable variant of HIF2α and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(63 citation statements)
references
References 85 publications
3
58
1
1
Order By: Relevance
“…We found a preferential stabilization of HIF-2α accompanied by a decrease in HIF-1α expression both in lungs and tumors from hypoxic mice. HIF-2α overexpression in a conditionally expressed mutant Kras G12D model of lung carcinogenesis resulted in larger tumors, similar to our findings with alveolar hypoxia (9). In patient non small cell lung cancer samples, HIF-1α and HIF-2α overexpression is frequently observed and correlates with the expression of angiogenic factors and poor outcome (35).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We found a preferential stabilization of HIF-2α accompanied by a decrease in HIF-1α expression both in lungs and tumors from hypoxic mice. HIF-2α overexpression in a conditionally expressed mutant Kras G12D model of lung carcinogenesis resulted in larger tumors, similar to our findings with alveolar hypoxia (9). In patient non small cell lung cancer samples, HIF-1α and HIF-2α overexpression is frequently observed and correlates with the expression of angiogenic factors and poor outcome (35).…”
Section: Discussionsupporting
confidence: 90%
“…It has been shown that the chronic inflammation characteristic of COPD can promote HIF stabilization by activation of NFκB (8). Mice that conditionally express both a non-degradable variant of HIF-2α and a mutant form of Kras (Kras G12D ) in the lungs developed larger and more invasive tumors, had an increased tumor burden and decreased survival compared with mice expressing only Kras G12D (9). Experiments with HIF-2α deletion unexpectedly demonstrated an increase in tumor burden, associated with a decrease in the candidate tumor suppressor gene Scgb3a1, revealing the complexity of the relationship between HIF-2α expression and tumorigenesis, in which either up or down regulation from basal expression can have similar effects (10).…”
Section: Introductionmentioning
confidence: 99%
“…A significant increase in HIF2α was observed in the RP-R-02LM. Increase in HIF2α has been reported to correlate with gene signatures of EMT in lung cancer models (42). We also observed an increase in expression of metastasis associated genes ALDH1A , E2F-1 , SETD2 and EZH2 (4245).…”
Section: Discussionmentioning
confidence: 99%
“…HIF-2α is over expressed in non-small lung carcinoma, renal carcinoma, and glioblastoma. Interestingly, HIF-2α cooperates with K-ras mutant to promote more invasive lung cancer [226]. This cancer is characterized by increased EMT, angiogenesis, and mobilization of endothelial progenitor cells [226].…”
Section: The P53/ta-p73/p63 C-myc Mir-29 Tumor Suppressor Pathwaymentioning
confidence: 99%
“…Interestingly, HIF-2α cooperates with K-ras mutant to promote more invasive lung cancer [226]. This cancer is characterized by increased EMT, angiogenesis, and mobilization of endothelial progenitor cells [226]. Further, HIF-2α has shown to be predominantly expressed in glioma stem cells compared with non-stem tumor cells and normal neural progenitors [227].…”
Section: The P53/ta-p73/p63 C-myc Mir-29 Tumor Suppressor Pathwaymentioning
confidence: 99%